Bio-Climatological Studies on Dry Matter Intake and Water Consumption of Growing Livestock - Somanathan V L (Department of Animal Management, College of Veterinary and Animal Sciences, 1980)
The present work was undertaken to study the distribution of climate at Mannuthy and to study the effect of the prevailing ambient temperature and relative humidity on the performance of growing crossbred cattle. The meterological data over a period of five years (1974 – 1978) were analysed to study the climatic picture of this locality. The rectal temperature, respiration rate, dry matter intake, water consumption and growth rate of eleven male and five female calves were observed for a period of twelve months. The climatic picture showed that there are two distinct seasons prevailing in this locality, namely, the dry and the rainy seasons, which are further sub divided into ‘Warm and dry’, ‘Hot and dry’, ‘Cold and wet’ and ‘Warm and wet’ seasons, respectively. The rectal temperature of the animals remained fairly constant throughout the year, inspite of wide variations in the ambient temperature. It showed negative correlation with ambient temperature (-0.357 in males and -0.207 in females) and positive correlation with relative humidity which was significantly only in males (0.416). The respiration rate varied from 30.973 per minute during July (lowest) to 49.230 per minute during April (highest). It showed positive correlation with ambient temperature (0.638 in males and 0.561 in females). Significant negative correlation between respiration rate and relative humidity was observed in males only (-0.253). The percentage dry matter intake was found to have a strong negative correlation with ambient temperature (-0.652 in males and -0.685 in females). Whereas with the relative humidity, the correlation was positive and was significant only in males (0.514). Highly significant positive correlation between ambient temperature and daily water consumption (0.763 in males and o.748 in females) and negative correlation between relative humidity and water consumption (-0.725 in males and -0.503 in females) were obtained in this study. There was negative correlation between ambient temperature and monthly weight gain and positive correlation between relative humidity and monthly weight gain, but was significant only in males. The negative correlation obtained in this case can be attributed to the poor quality of the roughage during the summer months rather than the direct effect of ambient temperature.